Advances in Speech-Language Pathology 2017
DOI: 10.5772/intechopen.70107
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Speech-Language Pathologies in Children

Abstract: Risk factors are understood to encompass "aspects of individual behavior or lifestyle, environmental exposure, hereditary or congenital characteristics that are associated with a health related condition". These are conditions that increase the chances of the child presenting speech-language disorders and that can be avoided, controlled, or treated. Risk is deined as the chance of a child exposed to certain factors (environmental or biological) to acquire or develop speech-language disorders. The objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
5
0
2
Order By: Relevance
“…The gender distribution in the current work reflects what has been already known about male predominance in communicative disorders. The explanation could be attributed to the cultural background, testosterone effect that hinder myelination which result in functional delayed maturation among male gender [26] . The gender distribution in semantic pragmatic type was nearly equal male and female affection.…”
Section: Discussionmentioning
confidence: 99%
“…The gender distribution in the current work reflects what has been already known about male predominance in communicative disorders. The explanation could be attributed to the cultural background, testosterone effect that hinder myelination which result in functional delayed maturation among male gender [26] . The gender distribution in semantic pragmatic type was nearly equal male and female affection.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that factors such as male gender, prematurity, shyness, being an only child, being the youngest child, bad oral habits, a family history of language impairment, and consumption of unsafe medications during pregnancy may affect children's LDD [11]. The present study aimed to evaluate, for the first time in Isfahan, the risk factors of LDD with idiopathic causes in children.…”
Section: Introductionmentioning
confidence: 94%
“…There are some factors, such as family history and gender, that might affect the children's communication skills development [20,21]. Family history of speech-language disorders is one of the risk factors for these impairments in children up to five years old [22]. Sunderajan and Kanhere [23], Molini-Avejonas et al [22], Saeed et al [24], and Conti-Ramsden and Durkin [25] highlighted the higher prevalence of speech-language impairments in children with positive family history.…”
Section: Introductionmentioning
confidence: 99%
“…Family history of speech-language disorders is one of the risk factors for these impairments in children up to five years old [22]. Sunderajan and Kanhere [23], Molini-Avejonas et al [22], Saeed et al [24], and Conti-Ramsden and Durkin [25] highlighted the higher prevalence of speech-language impairments in children with positive family history. Twin studies [26] and family aggregation studies [27], as well as genetic linkage analyses [28], provided strong evidence of running speech-language impairments in families.…”
Section: Introductionmentioning
confidence: 99%